POSSIBILITIES OF PREDICTING PREMATURE BIRTH - Дмитрий Евгеньевич Беглов; Оксана Николаевна Новикова; Наталья Владимировна Артымук (The Publishing House Medicine and Enlightenment, 2024)
The conducted scientific research is devoted to the problem of finding predictors of preterm birth, because the available tests either have low information content or are an expensive technique. The purpose of the study. To develop a computer program for predicting premature births among women in the Kemerovo region - Kuzbass. Materials and methods. To determine the most significant independent predictors of preterm birth, we conducted a study (n = 350), which analyzed more than 100 factors related to the development of preterm birth. As a result of binary logistic regression, four independent laboratory, clinical and paraclinical predictors of the risk of preterm birth were identified. Results. Based on the study, the most significant indicators affecting the risk of premature birth were identified. They include levels of prostaglandin class A antibodies, benzo[a]pyrene class G antibodies, cervical length at 18+0-20+6 weeks of pregnancy and smoking. Conclusion. You can use the program by clicking on the QR-code.